Morphometric analysis of flour, starch and protein of Tropaeolum tuberosum Ruiz and Pavón - Guevara-Freire, Deysi; Coello-Fiallos, Diana (Revista Mexicana de Ciencias Agrícolas, 2021)
Mashua (Tropaeolum tuberosum Ruiz and Pavón) is an edible tuber and was domesticated in the central Region of the Andes; it has little importance compared to other Andean crops, but it has great potential to be exploited in the industry. For this reason, the objective of this study was to determine the morphological characteristics of the starch, flour and freeze-dried protein of four mashua genotypes grown in the herbarium of the Faculty of Agricultural Sciences in 2018. Using the scanning electron microscope (MEB), the results showed flour granules with spherical, oval shapes with a diameter greater than and less than 6 μm and 5 μm in the yellow genotype (MA); 9.4 μm and 8.6 μm in the white genotype (MB), 8.3 μm and 6.9 in the yellow green genotype (MVA), 9.9 μm and 9.1 μm in the poza rondador genotype (MPR). Starch granules have sizes of 7.1 μm and 6.1 μm (MA), 18 μm and 16.3 μm (MB), 8.3 μm and 7.3 μm (MVA), 7 μm and 6.5 μm (MPR) with spherical, oval and spherical-truncated shapes. While the micrographs of the freeze-dried protein were observed sheets with sizes of 130, 221, 224 and 237 μm (MVA, MA, MB and MPR, respectively). The oval and spherical shape are highlighted in the flour and starch granules and the flattened polygonal shape in the protein, while the largest were the MB and MPR genotypes (starch and flour) and in the case of the MPR protein.